2012
DOI: 10.1111/j.1467-873x.2012.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

“I Like to Read, but I Know I’m Not Good at It”: Children’s Perspectives on High‐Stakes Testing in a High‐Poverty School

Abstract: A significant body of research articulates concerns about the current emphasis on high‐stakes testing as the primary lever of education reform in the United States. However, relatively little research has focused on how children make sense of the assessment policies in which they are centrally located. In this article, we share analyses of interview data from 33 third graders in an urban elementary school collected as part of a larger qualitative study of children's experiences in literacy in high‐poverty clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
(46 reference statements)
2
24
0
1
Order By: Relevance
“…The authors conclude with implications for teachers, noting, “this model also provides a strategy for teachers to assess the long‐term effects of peer‐group interaction on students” (p. 138). Other studies with traditional calls for future research and minimal calls for social action include Agiro (), Clarke (), and Dutro and Selland ().…”
Section: Resultsmentioning
confidence: 99%
“…The authors conclude with implications for teachers, noting, “this model also provides a strategy for teachers to assess the long‐term effects of peer‐group interaction on students” (p. 138). Other studies with traditional calls for future research and minimal calls for social action include Agiro (), Clarke (), and Dutro and Selland ().…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, much research over the past two decades suggests that the emphasis on testing constrains curriculum as well as teachers' attempts to provide students with rich learning experiences focused on higher-order inquiry (e.g., Abrams, Pedulla, & Madaus, 2003;Barksdale-Ladd & Thomas, 2000;Berliner, 2007;Darling-Hammond & Rustique-Forrester, 2005;Lomax, West, Harmon, Viator, & Madaus, 1995;Mathison & Freeman, 2003;McCarthey, 2008;Noddings, 2002;Zacher, 2011). Researchers have also found that some students respond with anxiety, faulty assumptions, frustration, or decreased motivation to the testing process and awareness of their scores (as these studies also find, certainly other students seem to take the process in stride or even enjoy it, particularly those who score well; e.g., Dutro & Selland, 2012;Enciso, 2001;Gershman, 2004;Jones et al, 1999;Perna & Thomas, 2009;Roderick & Engel, 2001;Wheelock, Bebell, & Haney, 2000). Indeed, post-NCLB reviews of the literature on high-stakes testing conclude that there is not convincing evidence that such testing has its intended effect of increasing student learning and may have unintended, significant negative consequences for students, especially those in high-poverty schools (Laitsch, 2006;Nichols, 2007).…”
Section: The Effects Of High-stakes Testsmentioning
confidence: 99%
“…Other studies reveal that high-stakes testing causes teachers to quit collaborative learning practice, integrated learning and inquiry-driven learning for the sake of isolated and split test practice in basic skills (Au, 2009;Barksdale-Ladd & Thomas, 2000;Dutro & Selland, 2012). It also causes students to be anxious, students' parents to be worried about their children's future, schools to bear strains to keep their reputation afloat, and induce dishonesty and cheating (Coniam & Falvey, 2018;Harris et al, 2011;Kempf, 2016;Thomas, 2005).…”
mentioning
confidence: 99%